Endothelial activation, cell-cell interactions, and inflammatory pathways in postoperative atrial fibrillation following cardiac surgery - Raquel López-Gálvez; José Miguel Rivera-Caravaca; Darío Mandaglio-Collados; Antonio J. Ruiz-Alcaraz; Álvaro Lahoz-Tornos; Diana Hernández-Romero; Esteban Orenes-Piñero; María Pilar Ramos-Bratos; Carlos M. Martínez; Marina Carpes; José María Arribas-Leal; Sergio Cánovas; et al. (Biomedical Journal, 2025)
Background: Postoperative atrial fibrillation (POAF) is common after cardiac surgery and related to endothelial activation and systemic inflammation. Herein, we investigate the pathophysiological mechanisms of AF through endothelial activation and cell-cell interactions related to the development of POAF. Methods: Patients without previous AF undergoing cardiac surgery were studied. Permanent AF patients were included as positive controls. Interleukin (IL)-6, Von Willebrand factor (vWF), N-terminal pro-brain natriuretic peptide (NT-proBNP), and high sensitivity troponin T (hsTnT) were evaluated by electrochemiluminescence. Vascular cell adhesion molecule-1 (VCAM-1) and human Growth Differentiation Factor 15 (GDF-15) were assessed by ELISA. Connexins (Cxs) 40 and 43 were measured by tissue immunolabelling, and apoptosis by TUNEL assay. Results: We included 117 patients (median age 67: 27.8% female): 17 with permanent AF; 27 with POAF, and 73 with non-AF. Patients with permanent AF and POAF had higher levels of NT-proBNP, hs-TnT, apoptotic nuclei, and decreased Cx43 expression, compared to non-AF patients (all p-value <0.05). VCAM-1 and GDF-15 were significantly higher in permanent AF vs. non-AF (p = 0.013 and p = 0.035). Conclusions: Greater endothelial activation and inflammation in AF patients compared to those without AF were found. The proinflammatory state in AF patients, in addition to the lower expression of Cx43, seems to be associated with atrial remodeling processes occurring in AF.